The Effect of Co-Branding, Celebrity Endorsers, and Electronic Word of Mouth on Purchase Intention with Brand Image as the Intervening Variable in the Quota of JKT48 Telkomsel Package - Anjani, Maryet Dwi; Dananjaya, Irwandaru (Eduvest - Journal of Universal Studies, 2025)
The telecommunications industry in Indonesia has undergone significant changes with the shift from legacy services to data-based services, influencing consumer behavior in accessing digital content and social media. The objective of this study is to determine whether Co-Branding, Celebrity Endorsers, and Electronic Word of Mouth directly affect Purchase Intention and indirectly affect Purchase Intention through Brand Image. The analysis method in this research employs quantitative primary data. The data used in this study were collected using a questionnaire instrument, with valid data gathered from 200 respondents. The testing stages include the measurement model (outer model) with convergent validity, discriminant validity, and reliability tests, as well as the structural model (inner model) with R-square tests, Q-square tests, SRMR tests, and hypothesis testing using path coefficients and specific indirect effects. The sampling method used in this study is non-probability sampling with purposive sampling technique. The testing tool utilized is SmartPLS 4. The results of this study indicate that Co-Branding has a positive and significant effect on Brand Image. However, Celebrity Endorser and Electronic Word of Mouth do not have a positive and significant effect on Brand Image. Co-Branding, Electronic Word of Mouth, and Brand Image have a positive and significant effect on Purchase Intention, whereas Celebrity Endorser does not have a positive and significant effect on Purchase Intention. Furthermore, Brand Image mediates the effect of Co-Branding on Purchase Intention, but does not mediate the effects of Celebrity Endorsers and Electronic Word of Mouth on Purchase Intention for the KuWOTAJKT48 package by Telkomsel.